Rational Pharmacological Approaches for Cognitive Dysfunction and Depression in Parkinson’s Disease - Sandoval-Rincón, Maritza; Sáenz-Farret, Michel; Miguel-Puga, Adán; Micheli, Federico; Arias-Carrión, Oscar (Frontiers in Neurology, 2015)
Parkinson´s disease (PD) is not a single entity but rather a heterogeneous neurodegenerative disorder. The present study aims to conduct a critical systematic review of the literature to describe the main pharmacological treatment strategies to treat cognitive dysfunction and major depressive disorder in PD patients. We performed a search of articles cited in PubMed from 2004 to 2014 using the following MeSH terms (Medical subject headings) “parkinson disease”; “Delirium”, “Dementia”, “Amnestic”, “Cognitive disorders” and “parkinson disease”; “depression”; “depressive disorder major”; “drug therapy”. We found a total of 71 studies related to pharmacological treatment in cognitive dysfunction and 279 studies for pharmacological treatment in major depressive disorder. After fulfillment of all the inclusion and exclusion criteria, 13 articles remained for cognitive dysfunction and 11 for major depressive disorder, which are presented and discussed in this study. Further research into non-motor symptoms of PD may provide insights into mechanisms of neurodegeneration, and provide better quality of life by using rational drugs.